(untitled) (Journal of Informatics Education and Research, 2024)
In general, the role of AI and IoT for increasing the performance level of businesses have been discussed here with the aim of establishing understandable data on such with several objectives regarding future potentials, business growth and relevant challenges. Therefore, how different industrial businesses are using these two variables in their workplace cultures have been prioritized in the entire study. Secondary qualitative research method has been followed throughout the research review work by aligning the systematic review and thematic analysis to get a clear overview about the topic. All the data have been collected in between the published year- 2017- 2021 based on several inclusion criteria for numerous relevant measures to conduct this one. The researcher has counted on all the essential methodological tools such as positivism philosophy, descriptive design and deductive approach to make the study reliable and well-visible. Furthermore, it has been proved that the selection of topics has been beneficial to get expected findings by using various journals in the similar regard. Hence, the conclusion section has illustrated how efficiently the researcher achieved the knowledge over the topic by focusing on its various relatable factors to improve the performances in businesses. Researching on such a topic based on current global scenario is found advantageous to move with the interest for further studies.